Comparing the kinematic characteristic of lower limb between diagonal and straight shot in forehand loop from world-class table tennis athlete - He, Y.; Yu, C.; Liang, Z.; Lv, X.; Zhou, Z.; Gu, Y. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
Diagonal shot (DS) and straight shot (SS) of forehand loop are the most common techniques in table tennis. The aim of this study was to investigate the differences in lower-limb kinematics between the DS and SS. A male Chinese table tennis participants performed the DS and SS in random order. Three-dimensional kinematic data were captured using eight-camera Vicon motion analysis system with a frequency of 200 Hz. Key findings from the study were that in the backwards-end (BE) phase, large significant differences in joint angles between DS and SS were found in the sagittal and transverse planes. Compared with DS, SS showed significantly larger knee external rotation with larger ankle external rotation and larger ankle adduction. In the forward-end (FE) phase, SS showed significantly larger knee adduction compared with DS. SS showed larger ankle abduction and internal rotation compared with DS. SS showed significantly larger knee internal rotation compared with DS. The results demonstrated that the SS requires a higher lower limb activity than a DS. These biomechanical findings may be beneficial for table tennis athletes and coaches as a method of optimizing performance characteristics for both competition and training.